Operational amplifiers and linear integrated circuits - Coughlin, Robert F; Driscoll, Fredericks F (New Delhi: Prentice Hall of India Private limited, 2010)
About the book: Operational Amplifiers, Linear Circuits, Electronics II, and Analog Circuit Design. This best-selling text presents a clear and interesting approach for op-amp courses while examining four basic active filters, illustrating 5-V digital logic ICs, and more. It provides many detailed, practical design and analysis examples intended to relate theory to the workplace.
Keywords: Electronic and Communication Engineering